Predictors and outcomes associated with the growth curves of self-efficacy beliefs in regard to anger and sadness regulation during adolescence: a longitudinal cross-cultural study - Di Giunta, Laura; Lunetti, Carolina; Lansford, Jennifer E.; Eisenberg, Nancy; Pastorelli, Concetta; Bacchini, Dario; Uribe Tirado, Liliana Maria; Iselin, Anne-Marie R.; Basili, Emanuele; Gliozzo, Giulia; Favini, Ainzara; Cirimele, Flavia; et al. (Frontiers in Psychology, 2023)
This longitudinal study examined unique and joint effects of parenting and negative emotionality in predicting the growth curves of adolescents’ self-efficacy beliefs in regard to regulating two discrete negative emotions (anger and sadness) and the association of these growth curves with later maladjustment (i.e., internalizing and externalizing problems). Participants were 285 children (T1: Mage = 10.57, SD = 0.68; 53.3% girls) and their parents (mothers N = 286; fathers N = 276) from Colombia and Italy. Parental warmth, harsh parenting, and internalizing and externalizing problems were measured in late childhood at T1, whereas early adolescents’ anger and sadness were measured at T2 (T2: Mage = 12.10, SD = 1.09). Adolescent self-efficacy beliefs in regard to anger and sadness regulation were measured at five time-points from T2 to T6 (T6: Mage =18.45, SD = 0.71), and internalizing and externalizing problems were measured again at T6. Multi-group latent growth curve models (with country as the grouping variable) demonstrated that in both countries there was on average a linear increase in self-efficacy about anger regulation and no change or variation in self-efficacy about sadness regulation. In both countries, for self-efficacy in regard to anger regulation (a) T1 harsh parenting and T1 externalizing problems were negatively associated with the intercept, (b) T2 anger was negatively associated with the slope, and (c) the intercept and the slope were associated with lower T6 internalizing and externalizing problems, controlling for T1 problems. For self-efficacy in regard to sadness regulation, (a) T1 internalizing problems were negatively associated with the intercept only in Italy, (b) T2 sadness was negatively associated with the intercept only in Colombia, and (c) the intercept negatively predicted T6 internalizing problems. This study advances knowledge of the normative development of self-efficacy beliefs in regard to anger and sadness regulation during adolescence across two countries, highlighting the predictive value of pre-existing family and individual characteristics on this development and prediction by the development of self-efficacy beliefs on later adjustment.